Validity of Physics E-Modules Based on an Inquiry Model Integrated with the Science, Environment, Technology, and Society Approach to 21st Century Skills - Westi Widia Wati; Syafriani Syafriani* (Universitas Syiah Kuala, 2023)
Education for the 21st century combines knowledge, abilities, and attitudes with a command of information and communication technologies. The role of education is very important as part of an effort to build national character and produce millennials who are innovative, creative, and ready to face global challenges. 21st-century skills are one of the skills that students must have to face global challenges. 21st century skills include critical thinking, creativity, collaboration, and communication, otherwise known as